Evaluation of antihyperlipidemic and antitumor activities of isolated coumarins from Salvadora indica. (January 2014) - Iyer, Deepa; Patil, U. K.
Abstract Context. Salvadora indica Wight (Salvadoraceae) contains a number of medically beneficial properties including abrasives, astringents and antiseptics. Traditionally, it was used by ancient Arabs to whiten and polish teeth. Objective: This study explores the antihyperlipidemic and antitumor effects of an ethanol extract of S. indica and its isolated phytoconstituents in rodents. Material and methods: Flash chromatography was used for the isolation of phytoconstituents from the stems of S. indica. An antihyperlipidemic study was carried out in Triton loaded rats. Animal groups were given intraperitoneal (i.p.) injection of Triton WR 1339 at dose of 400 mg/kg body weight (b.w.). Furthermore, antitumor activity was investigated in hybrid mice (of C57BL strain + Swiss albino strain). The animals were observed for tumor growth after injection of B16F10 melanoma cells into the dorsal skin of mice. Results: The stems of S. indica yielded xanthotoxin and umbelliferone through chromatographic separation techniques. The structures of the compounds were elucidated by spectroscopic data interpretation and showed antihyperlipidemic activity. The study showed significant reduction in total cholesterol (TC) (p < 0.01), triglycerides (TGs) (p < 0.001), low-density lipoproteins (p < 0.01) level whereas increased in high-density lipoprotein (p < 0.01) at a significant level, after the treatment. Pretreatment with the extract and phytoconstituents also showed delayed tumor growth by increasing the volume doubling time (VDT) (p < 0.01), growth delay (GD) (p < 0.01) and mean survival time (p < 0.001). Discussion and conclusion: Acute treatment caused a stimulatory effect on high density lipoprotein level and inhibition in TC and TG elevation induced by Triton. Tumor regression studies showed a regression response for tumor growth in vivo of murine mouse melanoma as demonstrated by increasing the VDT and GD.